Kolor pieniędzy. Filmowy styl Michaela Manna - Sitek, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
According to film studies experts, Michael Mann’s movies has the look and the smell of reality. The polisensoric character of his works is used to exhibit the aura of non-screen reality. Michael Mann uses narrative and stylistic elements to show the destructive side of social inequalities. In his genre films, he is presenting themes of social injustice and toxic corporate system (which are often hidden behind the elegant façade of late capitalism’s aesthetics).